Eksplorasi Pengaruh Dukungan Sosial dan Kontrol Diri terhadap Nomophobia pada Mahasiswa - Dicky Adi Pratama; Raihana Permata Ashfi (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2026)
Nomophobia, a modern psychological issue characterized by fear or anxiety when unable to access mobile phones, has become increasingly prevalent among university students. This study aims to examine the relationship between social support and self-control with nomophobia among undergraduate students. The research employed a quantitative correlational design with incidental sampling, involving 150 undergraduate students enrolled between 2021 and 2024. Data were collected through online questionnaires using three measurement scales, the Nomophobia Scale, the Social Support Scale, and the Self-Control Scale. Data were analyzed using multiple linear regression. The results showed that the overall model was significant (p = 0.00), indicating that social support and self-control jointly influence nomophobia. However, social support was not a significant predictor of nomophobia (t = 1.074; p = 0.285), whereas self-control demonstrated a significant negative relationship with nomophobia (t = −3.965; p = 0.000). In terms of effective contribution, self-control accounted for 9.5% of the variance in nomophobia, and social support contributed only 0.6%. In conclusion, the findings suggest that students with higher self-control tend to experience lower levels of nomophobia. These results imply the importance of developing self-regulation skills in educational settings to mitigate the risks associated with excessive mobile phone dependence.